Functionalization of extracellular matrix (ECM) on multichannel biphasic calcium phosphate (BCP) granules for improved bone regeneration. (July 2020) - Ventura, Reiza D.; Padalhin, Andrew R.; Lee, Byong Taek
Abstract: Extracellular matrix (ECM) was functionalized onto the surface of multi-channel biphasic calcium phosphate granules (MCG) to enhance its osteogenic potential and bone regeneration capacity. ECM functionalized MCG scaffolds contains collagen, sulfated glycosaminoglycan and trace amounts of growth factors such as bone morphogenic protein 2 (BMP-2) vascular endothelial growth factor (VEGF), transforming growth factor (TGF) and fibroblast growth factor (FGF). ECM functionalized MCG supported proliferation of MC3T3-E1 cells after 7 days. Improved protein adsorption in ECM functionalized MCG scaffolds was observed after 15 min of incubation. Osteogenic properties were improved in ECM functionalized MCG scaffolds based on ALP and mineralization of MC3T3-E1 cells after 7 and 14 days. Increased bone regeneration was observed in ECM functionalized MCG scaffolds implanted in rabbit femoral head defect after 4 and 8 weeks. Results showed that ECM functionalized MCG scaffolds enhanced bone regeneration and could be a promising biomaterial in bone regeneration application. Graphical abstract: Schematic diagram of the functionalization of multi-channel BCP granules with decellularized extracellullar matrix (ECM) derived from porcine skin implanted in femoral defect for 2 months. Unlabelled Image Highlights: Multi-channel biphasic calcium phosphate granules (MCG) were functionalized by decellularized porcine skin ECM. ECM-MCG functionalization was performed using EDC/NHS-chemical conjugation mechanism. The optimized scaffold (15ECM-MCG) was biocompatible and improved osteogenic differentiation. 15ECM-MCG scaffold ensured bone regeneration at 8 weeks through rabbit femoral head defect model.